Praktik Akuntansi Pemerintahan di Indonesia: Persamaan, Teknik Penjurnalan, dan Tantangan Transaksi - Walidin, Bahrul; Bayani, Shahibul; Haya, A’qilla Fadia; Khaddafi, Muammar (JURNAL ONLINE INSAN AKUNTAN; Vol 10 No 1 (2025): Jurnal Online Insan Akuntan (Juni 2025), 2025)
This paper aims to analyze government accounting practices in Indonesia, focusing on the application of accounting equations, journalizing techniques, and the challenges faced in managing public sector transactions. Using a systematic literature review approach, this study synthesizes various national literature and government policy documents published between 2019 and 2024. The analysis reveals that inconsistencies in journalizing, lack of competent human resources, and the complexity of non-routine transactions are the main challenges in government accounting implementation. Furthermore, differences in interpreting government accounting standards often lead to discrepancies in financial reporting. This paper also highlights the role of information technology as a strategic solution to enhance efficiency, accuracy, and transparency in governmental financial management. The findings are expected to provide insights and recommendations for policymakers and practitioners in improving the quality and accountability of government accounting practices in Indonesia..   Keywords : Government Accounting, Journalizing Techniques, Transaction Challenges